An Application of Business Process Management to Health Care Facilities. Issue 2 (April 2017) - Hassan, Mohsen M. D.
Abstract : The purpose of this article is to help health care facility managers and personnel identify significant elements of their facilities to address, and steps and actions to follow, when applying business process management to them. The ABPMP (Association of Business Process Management Professionals) life-cycle model of business process management is adopted, and steps from Lean, business process reengineering, and Six Sigma, and actions from operations management are presented to implement it. Managers of health care facilities can find in business process management a more comprehensive approach to improving their facilities than Lean, Six Sigma, business process reengineering, and ad hoc approaches that does not conflict with them because many of their elements can be included under its umbrella. Furthermore, the suggested application of business process management can guide and relieve them from selecting among these approaches, as well as provide them with specific steps and actions that they can follow. This article fills a gap in the literature by presenting a much needed comprehensive application of business process management to health care facilities that has specific steps and actions for implementation.